Canopy and Ear Traits Associated With Avoidance of Fusarium Head Blight in Wheat - Jones, Stephen; Farooqi, Arifa; Foulkes, John; Sparkes, Debbie L.; Linforth, Robert; Ray, Rumiana V. (Frontiers in Plant Science, 2018)
Doubled haploid and elite wheat genotypes were ground inoculated in three field experiments and head spray inoculated in two glasshouse experiments, using mixed Fusarium and Microdochium species, to identify crop canopy and ear traits associated with Fusarium head blight (FHB) disease. In all experiments, flag leaf length and tiller number were consistently identified as the most significant canopy traits contributing to progression of FHB caused by Fusarium. graminearum, F. culmorum and F. avenaceum. The influence of ear traits was greater for F. poae that may possess more diverse routes for transmission and spread. Consistently, spikelet density was associated with increased disease severity in the field. F. graminearum, F. culmorum and F. langsethiae were the main mycotoxin producers and their respective toxins were significantly related to fungal biomass and number of spikelets per ear. Genotypes with lower tiller numbers, shorter flag leaves and less dense ears maybe able to avoid FHB disease caused by F. graminearum, F. culmorum, F. avenaceum or Microdochium species, however selection for these canopy and ear architectural traits to enable disease avoidance in wheat is likely to result in a potential trade-off with grain yield and therefore only moderately advantageous in susceptible genotypes.